Modeling the Transport and Deposition of 10Be Produced by the Strongest Solar Proton Event During the Holocene. Issue 13 (28th June 2022) - Spiegl, T. C.; Yoden, S.; Langematz, U.; Sato, T.; Chhin, R.; Noda, S.; Miyake, F.; Kusano, K.; Schaar, K.; Kunze, M.
Abstract: Prominent excursions in the number of cosmogenic nuclides (e.g., 10 Be) around 774 CE/775 document the most severe solar proton event (SPE) throughout the Holocene. Its manifestation in ice cores is valuable for geochronology, but also for solar‐terrestrial physics and climate modeling. Using the ECHAM/MESSy Atmospheric Chemistry (EMAC) climate model in combination with the Warning System for Aviation Exposure to SEP (WASAVIES), we investigate the transport, mixing, and deposition of the cosmogenic nuclide 10 Be produced by the 774 CE/775 SPE. By comparing the model results to the reconstructed 10 Be time series from four ice core records, we study the atmospheric pathways of 10 Be from its stratospheric source to its sink at Earth's surface. The reconstructed post‐SPE evolution of the 10 Be surface fluxes at the ice core sites is well captured by the model. The downward transport of the 10 Be atoms is controlled by the Brewer‐Dobson circulation in the stratosphere and cross‐tropopause transport via tropopause folds or large‐scale sinking. Clear hemispheric differences in the transport and deposition processes are identified. In both polar regions the 10 Be surface fluxes peak in summertime, with a larger influence of wet deposition on the seasonal 10 Be surface flux in Greenland than in Antarctica. Differences in the peak 10 Be surface flux following the 774 CE/775 SPE at the drilling sites are explained by specific meteorological conditions depending on the geographic locations of the sites. Plain Language Summary: During large solar storms, high energy particles are hurled with enormous force toward Earth by the Sun. As these particles collide with atmospheric constituents (such as oxygen or nitrogen) unique nuclides of cosmogenic origin are formed in the higher atmosphere. From there they are transported downwards and finally precipitate at the surface due to different sink processes. Their imprints can be conserved over thousands of years within natural archives, such as ice cores or tree rings. Analysis of these natural archives around the globe indicates that the strongest solar storm over the last 10.000 years happened around 774 CE/775. This event is estimated to have been up to two orders of magnitude stronger, than the strongest known events documented for the satellite era. In this study, we model and analyze the transport and deposition of the cosmogenic nuclides produced by the extreme 774 CE/775 event, by applying a new experimental setup. Our results might help to interpret the fingerprints of historical extreme events with respect to the prevailing atmospheric conditions. Key Points: The modeled transport and deposition of the cosmogenic nuclide 10 Be produced by the 774/775 solar proton event was compared to 10 Be ice core records Hemispheric differences in stratospheric and cross‐tropopause transport, and deposition were identified, with polar summertime maxima of 10 Be surface flux Differences in reconstructed 10 Be surface fluxes are explained by the local ratio of wet to dry deposition maximizing inthesummertime